The Phenolic Compound from Kalanchoe blossfeldiana (Crassulaceae) Leaf and Its Antiplasmodial Activity against Plasmodium falciparum 3D7 - Yenny Febriani Yun; Faizal Hermanto; Lilis Siti Aisyah; Tri Reksa Saputra; Arif Rahman Hakim; Ade Kania Ningsih; Tati Herlina; Euis Julaeha; Achmad Zainuddin; Unang Supratman (Indonesian Journal of Chemistry, 2016)
Various species of Kalanchoe plants have been widely used as raw materials in traditional medicines. This study was the continuation of the researches on secondary metabolites from Indonesia Kalanchoe plants, focused on Kalanchoe blossfeldiana. Fresh K. blossfeldiana leaf was extracted with methanol at room temperature to obtain the concentrated extract. The concentrated methanol extract was dissolved in water and then partitioned successively with n-hexane and ethyl acetate. The methanol, n-hexane, ethyl acetate extracts were tested using antiplasmodial assay against Plasmodium falciparum 3D7. The IC50 of methanol, n-hexane, and ethyl acetate extract were 13.002; 2.807, and 11 nM, respectively. Ethyl acetate extract was separated by the combination of chromatography on silica and ODS. This process produced the yellow solid. The chemical structure of the compound was determined based on UV, IR, MS, 1H-NMR, and 13C-NMR analyses and the comparison of data obtained from the literature and identified as phenolic compound, namely 3,3',4',5,7-pentahydroxyflavone or quercetin (1), and displayed antiplasmodial activity with IC50 3.97x10-2 nM.